Early lineage switch from T-acute lymphoblastic leukaemia to common B-all. - Hafiza, A; Azura, AH; Azma, RZ; Azlin, I; Zarina, AL; Hamidah, NH (Penerbit UKM, 2011)
Leukaemic stem cells have heterogenous differentiation potential. The immunophenotypes of blast cells are usually consistent throughout the disease course even at relapse. Rarely, blast cells may undergo a ‘lineage switch’ during the course of disease especially during relapse. We would like to highlight such a case in a 10-year old boy who presented with a two weeks history of lethargy, poor appetite, low grade fever, respiratory distress, cardiac failure, generalized oedema and hepatosplenomegaly. Full blood count showed a leucocyte count of 41.5x109/L and platelet count of 37x109/L. The peripheral blood film showed presence of numerous blast cells. Bone marrow aspiration revealed a hypercellular marrow, which consisted of mainly blast cells with high nuclear to cytoplasmic ratio and inconspicuous nucleoli. Immunophenotyping and cytochemistry results were consistent with the diagnosis of T-cell acute lymphoblastic leukaemia. The patient achieved remission after treatment with UK ALL 97 protocol, regime B chemotherapy. However, he relapsed seven months after the initial diagnosis with 26% blast cells in the bone marrow aspirate. The majority was L1 blast cells admixed with some L2 blast cells. Immunophenotyping was consistent with common precursor B acute lymphoblastic leukaemia. The treatment was changed to a more lineage specific chemotherapy. Nonetheless, the patient never achieved remission and was planned for palliative management. This case illustrated a unique and rare case of rapid lineage switch from T-cell acute lymphoblastic leukaemia to common precursor B-cell acute lymphoblastic leukaemia.